Excavations at Chester : medieval and post-medieval development within the northern and eastern suburbs to c.1900 - Dodd, Leigh, (Archaeopress Archaeology, 2021)
'Excavations at Chester' brings together for the first time the results from archaeological investigations carried out within the suburbs to the north and east of the Medieval and later City of Chester between 2002 and 2018. At sites investigated to both the north and east of the City, significant stretches of the defensive ditch cut during the Civil War of the 17th century were excavated. The results bring into question the accepted lines of these massive defensive outworks. To the northwest of the City, the findings demonstrate that the land remained agricultural until late in the 18th century and was not truly developed until the arrival of the canal network. To the north of the City, development of terraced housing had begun by the 1830s, shortly before the arrival of the railway network, in the area that would become the suburb of Newtown.